Hubungan indeks massa tubuh dengan forced vital capacity pada usia remaja - Sembel, Imanuela Maretha Julia; Polii, Hedison; Engka, Joice Nancy Ansje (UNIVERSITAS SAM RATULANGI, 2024)
Background: The respiratory system plays an important role in the human body. However, body mass index (BMI) affects lung volume, and obesity is associated with changes in lung volume. Obesity can also reduce static and dynamic lung volumes. Aim: To determine the relationship between adolescent BMI and forced vital capacity (FVC). Methods: This study uses an analytical observational research design using a cross-sectional study research design. Sampling is done using a purposive sampling technique. Data collection by measuring body weight and height to calculate body mass index, and measuring FVC using a spirometer. Data analysis using normality test and Spearman correlation test. Results: Data normality tests were the Kolmogorov-Smirnov test and were not normally distributed data. We used the Spearman correlation test to determine whether there was a relationship between FVC and BMI using SPSS Statistics. The results obtained were a correlation coefficient value of 0.288 with p-value =0.008 (p=<0.05), which means there is a relationship between FVC and BMI. Conclusion: There is a significant positive relationship between FVC and body mass index, where the higher the FVC, the higher the body mass index. Keywords: body mass index, forced vital capacity (FVC)